Supporting Maintenance Management System (SMMS) for MARA College Kuala Nerang - Rizanawati, Ramli (2011)
The system technologies are rapidly increasing uses in routine daily work specifically for the administration department applications in organizations. The aim of the study is to design and develop the Supporting Maintenance Management System for MARA College Kuala Nerang (SMMS), Kedah. SMMS is an online report application system which provides a convenient graphics user interface (GUI) for staff, technician and administration staff. This system allows users to do any report regarding to the equipments break down or malfunctioning equipment. The methodology for developing the prototype is derived from the System Development Life Cycle (SDLC) framework and contained only these four phases (i) Requirement analysis, (ii) Design, (iii) Develop and (iv) Evaluate the prototype. The UML model is used to model the system requirement, Active Server Pages (ASP) language and HTML coding is used to develop the prototype. Technology Acceptance Model (TAM) is used to evaluate the prototype which thirty two (32) staffs of MARA College Kuala Nerang are involved in this process. The significant of the study are the maintenance report will be done via online without using any application form, reduce application processing time and save time, cost and energy of the staff especially to those who are busy in daily work.